Evaluation of [F-18]F-DPA PET for Detecting Microglial Activation in the Spinal Cord of a Rat Model of Neuropathic Pain - Shimochi Saeka; Keller Thomas; Kujala Ella; Khabbal Joonas; Rajander Johan; Löyttyniemi Eliisa; Solin Olof; Nuutila Pirjo; Kanaya Shigehiko; Yatkin Emrah; Grönroos Tove J.; Iida Hidehiro (SPRINGER, 2025)
Purpose
Recent studies have linked activated spinal glia to neuropathic pain. Here, using a positron emission tomography (PET) scanner with high spatial resolution and sensitivity, we evaluated the feasibility and sensitivity of N,N-diethyl-2-(2-(4-([18F]fluoro)phenyl)-5,7-dimethylpyrazolo[1,5-a] pyrimidin3-yl)acetamide -([F-18]F-DPA) imaging for detecting spinal cord microglial activation after partial sciatic nerve ligation (PSNL) in rats.
Procedures
Neuropathic pain was induced in rats (n = 20) by PSNL, and pain sensation tests were conducted before surgery and 3 and 7 days post- injury. On day 7, in vivo PET imaging and ex vivo autoradiography were performed using -[F-18]F-DPA or -[C-11]PK11195. Ex vivo biodistribution and PET imaging of the removed spinal cord were carried out with -[F-18]F-DPA. Sham-operated and PK11195pretreated animals were also examined.
Results
Mechanical allodynia was confirmed in the PSNL rats from day 3 through day 7. Ex vivo autoradiography showed a higher lesion-to-background uptake with -[F-18]F-DPA compared with -[C-11]PK11195. Ex vivo PET imaging of the removed spinal cord showed -[F-18]F-DPA accumulation in the inflammation site, which was immunohistochemically confirmed to coincide with microglia activation. Pretreatment with PK11195 eliminated the uptake. The SUV values of in vivo -[F-18]F-DPA and -[C-11]PK11195 PET were not significantly increased in the lesion compared with the reference region, and were fivefold higher than the values obtained from the ex vivo data. Ex vivo biodistribution revealed a twofold higher -[F-18] F-DPA uptake in the vertebral body compared to that seen in the bone from the skull.
Conclusions
[F-18]F-DPA aided visualization of the spinal cord inflammation site in PSNL rats on ex vivo autoradiography and was superior to -[C-11]PK11195. In vivo -[F-18]F-DPA PET did not allow for visualization of tracer accumulation even using a high-spatial-resolution PET scanner. The main reason for this result was due to insufficient SUVs in the spinal cord region as compared with the background noise, in addition to a spillover from the vertebral body.